HARMONIZATION OF GOVERNMENT BUREAUCRACY TO REALIZE GOOD GOVERNANCE - Sulistya Eviningrum; Arief Budiono (Media Keadilan: Jurnal Ilmu Hukum, 2022)
This article analyzes the harmonization of governmental bureaucracy to achieve good governance. The results of this research show that some things that are related to good governance are public policies, participative public policies, reform of a governmental bureaucracy, and social empowerment. Public policies must be derived in a set of implementing guidelines and technical guidelines that apply internally in a bureaucracy. Apart from formally fulfilling society's public rights, inspiring public policies are involved in the development plans of a particular area. A clear and consistent instrument is also created to develop a mechanism of social participation. The reformation of governmental bureaucracy to achieve good governance is directed to the change process and the target achievement that includes: a) the actualization of a value system that becomes the basis and the reference for a behavioral system of good governance, b) structure: the state or social institutional order at every area unit, c) process (management in all of its functions, in the activity dynamics and the public and private entities), d) apparatus resources. Social empowerment through the good governance mechanism will lead to co-guiding, co-steering, and co-managing processes.Keywords: Bureaucratic Harmonization; Government; Good Governance. ABSTRAKArtikel ini menganalisis harmonisasi birokrasi pemerintah untuk mencapai tata kelola pemerintahan yang baik. Hasil penelitian ini menunjukkan bahwa beberapa hal yang berkaitan dengan tata kelola pemerintahan yang baik adalah kebijakan publik, kebijakan publik partisipatif, reformasi birokrasi pemerintahan, dan pemberdayaan sosial. Kebijakan publik harus diturunkan dalam seperangkat pedoman pelaksana dan pedoman teknis yang berlaku secara internal dalam birokrasi. Terlepas dari secara resmi memenuhi hak-hak publik masyarakat, kebijakan publik yang menginspirasi terlibat dalam rencana pembangunan daerah tertentu. Instrumen yang jelas dan konsisten juga diciptakan untuk mengembangkan mekanisme partisipasi sosial. Reformasi birokrasi pemerintahan untuk mencapai tata kelola pemerintahan yang baik diarahkan pada proses perubahan dan pencapaian target yang meliputi: a) aktualisasi sistem nilai yang menjadi dasar dan acuan sistem perilaku tata kelola pemerintahan yang baik, b) struktur: tata tertib kelembagaan negara atau sosial di setiap unit wilayah, c) proses (manajemen dalam semua fungsinya,  dalam dinamika kegiatan dan entitas publik dan swasta), d) sumber daya aparatur. Pemberdayaan sosial melalui mekanisme tata kelola yang baik akan mengarah pada proses co-guiding, co-steering, dan co-managing.